Pour un théâtre de la présence : Diderot du théâtre au roman - Scott, Anne (Man and Nature / L'homme et la nature, 1984)
Given the intensely dramatic reality of works like Le Neveu de Rameau and Le Paradoxe sur le comédien, why should Diderot's plays be so wooden and static? The most important reason is that Diderot's drama is constituted primarily by interaction between writer and reader, and disappears with the eighteenth-century theatre's requirement of "objective" action.